2017
DOI: 10.1242/jcs.198242
|View full text |Cite
|
Sign up to set email alerts
|

Derlin-1 promotes ubiquitylation and degradation of the epithelial Na+ channel, ENaC

Abstract: Ubiquitylation of the epithelial Na + channel (ENaC) plays a critical role in cellular functions, including transmembrane transport of Na + , Na + and water balance, and blood pressure stabilization. Published studies have suggested that ENaC subunits are targets of ER-related degradation (ERAD) in yeast systems. However, the molecular mechanism underlying proteasome-mediated degradation of ENaC subunits remains to be established. Derlin-1, an E3 ligase mediator, links recognized target proteins to ubiquitin-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
(36 reference statements)
2
24
0
Order By: Relevance
“…Indeed, several molecular chaperones have been implicated in key steps during ENaC biogenesis, including subunit folding and channel assembly within the ER (30,31). Other factors regulate intracellular trafficking, plasma membrane insertion, and retrieval as well as both ER-associated and lysosome-mediated degradation of ENaC (32)(33)(34)(35)(36)(37). Together, this multistage machinery impacts the total number of channels (N) at the cell surface.…”
mentioning
confidence: 99%
“…Indeed, several molecular chaperones have been implicated in key steps during ENaC biogenesis, including subunit folding and channel assembly within the ER (30,31). Other factors regulate intracellular trafficking, plasma membrane insertion, and retrieval as well as both ER-associated and lysosome-mediated degradation of ENaC (32)(33)(34)(35)(36)(37). Together, this multistage machinery impacts the total number of channels (N) at the cell surface.…”
mentioning
confidence: 99%
“…Growing evidence now supports the ubiquitination of target proteins in the pathogenesis of a variety of diseases, including kidney injury . The attachment of ubiquitin (8.5 kDa) to a substrate protein requires three distinct enzymes and steps.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence now supports the ubiquitination of target proteins in the pathogenesis of a variety of diseases, including kidney injury. 25,27,28 The attachment of ubiquitin (8.5 kDa) to a substrate protein requires three distinct enzymes and steps. The first step activates ubiquitin by forming a thioester linkage between the E1 ubiquitin-activating enzyme and the autophagy-related phagophore-formation transporter (APT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that co-expression of PON3 reduced ENaC whole cell expression in FRT cells, suggesting that this trimeric channel is less stable in the presence of PON3. Molecular chaperones have important roles in ENaC quality control within the early secretory pathway (34,42,102). It is possible that PON3 facilitates proteasomal degradation of misfolded ENaC subunits.…”
Section: Discussionmentioning
confidence: 99%